ئیستاتیکا لە شیعرەکانی ( سەلاح محەمەد) دا - عەبدوڵا, پ٠ی٠د٠ عەباس ساڵح (Sulaimani Journal for Humanities, 2023)
Salah Muhammad was one of the Kurdish poets of the period between late 1970s, 1980s and 1990s. He was a renowned voice in Kurdish poetry particularly in Sulaimani. His poetic works have largely been left unattended. Hence this paper is written to shed light on his thought and poetic position by analyzing the aesthetics of some of his texts mainly from the perspective of language and poetic imagery. Moreover, the study is both theoretical and practical by adopting a descriptive – analytical method. The study falls into two main parts: The first deals with the concept and definition of aesthetics and the second highlights the types of aesthetics in the poems written by the poet.
Keywords: poet; aesthetics; language poetic; imagery poetic